Math
posted by fishbowl .
simplify the expression
2log(4)9log(2)3
*(base)
i know the answer is log(2)3 but i can't figure out the work to get that answer

Use the rules for changing the base of a logarithm at
http://oakroadsystems.com/math/loglaws.htm#NewBase
It says that
log(a)x = log(b)x/log(b)a
In your case, use it to show that
log(4)9 = log(2)3^2/log(2)4
= 2log(2)3/log(2)4 = log(2)3 !!
Therefore 2log(4)9 = 2 log(2)3
Subtracting 2log(2)3 from that leaves you with log(2)3 
The last line should read:
Subtracting log(2)3 from 2log(2)3 leaves you with log(2)3
Respond to this Question
Similar Questions

LOGARITHMS
HI THE QUESTION STATES THAT ONE SHOULD CALCULATE THE LOGS WITHOUT THE USE OF A CALCULATOR...OKAY MY PROBLEM IS THIS... 2 3 2log 8 + 2log 8 what should i do? 
math(Please help)
1) use the properties of logarithms to simplify the logarithmic expression. log base 10 (9/300) log  log 300 log 9 = 2 log 3 log 300 = log 3 + log 100 = log 3+2 I just do not know how to put these together now! 
Math
these are some problems i do not get any help is appreciated. These are copied exactly from the worksheet so i don't think i wrote anything wrong. Please explain it for me and could i get the answer thanks (: Log7 x= ½ log7 36 (log … 
algebra 2 logs and trig
log(base 2)cotx  2log(base 4)csc2x = log(base 2)cosx the answer should be x = pi/3, 5pi/3 not sure how to work it out though, any help? 
Precalc
1. 1/3log base 8 of (x+1)=2log base 8 of 3(2/3)log base 8 of (x+1) 2. 2^x+8 times 2^=x all over 2 = 3 3. if log base a of 3= x and log base a of 2 = y, find each of thefollowing in terms of x and y log base a (18a^3) thanks!! 
Algebra 2
Explain the difference between log base b (mn) and ( log base b of m)(log base b of n). Are they equivalent? 
Advanced Functions/ Precalculus Log
1. Evaluate 4^(log base4 64) + 10^(log100) 2. Write 1+log(base2)x^3 as a single logarithm 3. Write log(base b)√(x^3 y z^6) 4. Solve log(base 2)xlog(base 2)6=log(base 2)5+2log(base 2)3 5. Solve 3^(2x) = 9(81^x) 6. Solve 3^(2x)=7^(3x1). … 
Calculus
Please help simplify this expression: 2 log (base 4) ^9  log (base 2) ^3 The answer should be log(base 2) ^3 
precalc
Solve: round to the thousandths if necessary! 1) 4^3/4x+5 = 12 2) log(x1) + log x = log 6 3) 2log(base 4) 5  log(base 4) x + log(base 4) 3  log(base 4) 7 = 1/2 
Econ math/logarithms
If log with base b (2)=0.39 and log with base b (3)=0.61 evaluate the following. log with base b (8). Simplify your answer. How to start?